FTKPM Senior Project Showcase presents 146 research projects - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 21 June 2023 – Concerned with the community involved in drying fishery products has given the idea to two Universiti Malaysia Pahang (UMP) students to produce an innovative solar house dryer equipped with an additional heater in a research project titled “Go Green Dryer Prototype for Agriculture and Marine Product”.